(untitled) (Research, Society and Development, 2021)
Anticarsia gemmatalis is one of the most important pests in world soybean crop. The most common intervention is the application of agrochemicals, such as novaluron and glyphosate. Among biological control agents, much attention has been drawn to entomopathogenic fungi, as Metarhizium rileyi. Here, we examined the changes that occur in the immune system (total and differential hemocyte count), secondary effects (caterpillar morphology), and oxidative metabolism after the caterpillars were exposed to M. rileyi, novaluron or glyphosate. M. rileyi was able to induce changes in the width, length, and weight of A. gemmatalis pupae, along with an increased in the number of defense cells. Novaluron prompt changes the insect’s immunity, and glyphosate caused milder immunological effects. However, it caused significant secondary effects including malformations in pupae and adults, and an increase in nitric oxide (NO) levels. Mortality observed when treating insects with novaluron and malformations due to glyphosate treatments did not occur due to oxidative stress. However, when insects were exposed to M. rileyi, we verified significantly increased levels of NO and concluded that these insects died due to oxidative stress. Our data provide evidence that contributes to better understanding the mechanism of herbicide-fungus interaction in the management of Anticarsia gemmatalis.